Role of sex in lung cancer risk prediction based on single low-dose chest computed tomography - Judit Simon; Peter Mikhael; Ismail Tahir; Alexander Graur; Stefan Ringer; Amanda Fata; Yang Chi-Fu Jeffrey; Jo-Anne Shepard; Francine Jacobson; Regina Barzilay; Lecia V. Sequist; Lydia E. Pace; et al. (Scientific Reports, 2023)
Abstract A validated open-source deep-learning algorithm called Sybil can accurately predict long-term lung cancer risk from a single low-dose chest computed tomography (LDCT). However, Sybil was trained on a majority-male cohort. Use of artificial intelligence algorithms trained on imbalanced cohorts may lead to inequitable outcomes in real-world settings. We aimed to study whether Sybil predicts lung cancer risk equally regardless of sex. We analyzed 10,573 LDCTs from 6127 consecutive lung cancer screening participants across a health system between 2015 and 2021. Sybil achieved AUCs of 0.89 (95% CI: 0.85–0.93) for females and 0.89 (95% CI: 0.85–0.94) for males at 1 year, p = 0.92. At 6 years, the AUC was 0.87 (95% CI: 0.83–0.93) for females and 0.79 (95% CI: 0.72–0.86) for males, p = 0.01. In conclusion, Sybil can accurately predict future lung cancer risk in females and males in a real-world setting and performs better in females than in males for predicting 6-year lung cancer risk.